Pengembangan Kapasitas Manajemen LKSA Guyub Rukun Kota Bengkulu - Yessilia Osira; Nurlianti Muzni (UNIB Press, 2021)
Development of Management Capacity of LKSA Guyub Rukun Bengkulu City. Capacity building is a process, which is carried out at three levels, namely individuals, groups, and institutions or organizations, in this case, the LKSA Guyub Rukun. This process is carried out to ensure the continuity of the organization through the achievement of the goals and objectives of the organization concerned. In this regard, the community service activities carried out as a form of follow-up to the cooperation agreement between the Faculty of social and Political Sciences, Bengkulu University, and LKSA Guyub Rukun Bengkulu City, have the following objectives: 1) Assist the LKSA Guyub Rukun Management in managing the administration of the institution's activities. 2) Assist the LKSA Guyub Rukun Management in scheduling various children's activities at the institution. 3) Assist the LKSA Guyub Rukun Management in preparing the process of implementing institutional accreditation. The results of service activities are ultimately a form of assistance in the accreditation process carried out by LKSA Guyub Rukun, which includes an assessment of 6 accreditation standards: standard 1 (services to inmates), standard 2 (the process of social worker practice service), standard 3 (organizational management), standard 4 (human resources), standard 5 (facilities and infrastructure, and standard 6 (outcomes of institutional services). Keywords: Capacity building, LKSA management, accreditation